Effects of targeting the transcription factors Ikaros and Aiolos on B cell activation and differentiation in systemic lupus erythematosus. Issue 1 (16th March 2021) - Rivellese, Felice; Manou-Stathopoulou, Sotiria; Mauro, Daniele; Goldmann, Katriona; Pyne, Debasish; Rajakariar, Ravindra; Gordon, Patrick; Schafer, Peter; Bombardieri, Michele; Pitzalis, Costantino; Lewis, Myles J
Abstract : Objective: To evaluate the effects of targeting Ikaros and Aiolos by cereblon modulator iberdomide on the activation and differentiation of B-cells from patients with systemic lupus erythematosus (SLE). Methods: CD19 + B-cells isolated from the peripheral blood of patients with SLE (n=41) were cultured with TLR7 ligand resiquimod ±IFNα together with iberdomide or control from day 0 (n=16). Additionally, in vitro B-cell differentiation was induced by stimulation with IL-2/IL-10/IL-15/CD40L/resiquimod with iberdomide or control, given at day 0 or at day 4. At day 5, immunoglobulins were measured by ELISA and cells analysed by flow cytometry. RNA-Seq was performed on fluorescence-activated cell-sorted CD27 - IgD + naïve-B-cells and CD20 low CD27 + CD38 + plasmablasts to investigate the transcriptional consequences of iberdomide. Results: Iberdomide significantly inhibited the TLR7 and IFNα-mediated production of immunoglobulins from SLE B-cells and the production of antinuclear antibodies as well as significantly reducing the number of CD27 + CD38 + plasmablasts (0.3±0.18, vehicle 1.01±0.56, p=0.011) and CD138 + plasma cells (0.12±0.06, vehicle 0.28±0.02, p=0.03). Additionally, treatment with iberdomide from day 0 significantly inhibited the differentiation of SLE B-cells into plasmablasts (6.4±13.5 vs vehicle 34.9±20.1, p=0.013) and antibody production. When given at later stages of differentiation, iberdomide did not affect the numbers of plasmablasts or the production of antibodies; however, it induced a significant modulation of gene expression involving IKZF1 and IKZF3 transcriptional programmes in both naïve B-cells and plasmablasts (400 and 461 differentially modulated genes, respectively, false discovery rate<0.05). Conclusion: These results demonstrate the relevance of Ikaros and Aiolos as therapeutic targets in SLE due to their ability to modulate B cell activation and differentiation downstream of TLR7.